A character-based management model of pesantren education for strengthening students’ nationalism and patriotism - Hadi, Sukandar; Idrus, Ali; Sulistiyo, Urip (Universitas Jambi, Indonesia, 2026)
This study explores a character-based management model in three pesantren in Merangin Regency, Indonesia, aimed at strengthening students’ nationalism and patriotism. Using a qualitative descriptive approach, data were gathered through interviews, observations, and document analysis involving kyai, teachers, and administrators. The findings reveal that although each pesantren applies distinct managerial styles, all embed national values through integrated planning, curriculum design, extracurricular programs, and moral leadership. The kyai plays a central role in shaping institutional culture and modeling civic values. Effective character formation emerges from a combination of traditional Islamic practices and responsive educational management. The study formulates a contextualized model that merges cultural authenticity with managerial structure, offering a practical framework for pesantren and similar institutions to cultivate national identity through education.